About Galatians, apocalyptic and the switching of paradigms - Gys M. H. Loubser (Acta Theologica)
The article indicates that although apocalyptic is probably not the hermeneutical key par excellence to Pauline theology, it does lie at the heart of Pauline theology and should be thoroughly accounted for in Galatians. Paul employs apocalyptic in Galatians to stress the radical soteriological and ethical change brought about by the advent of Christ and his Spirit. He wished to reframe his readers’ thought world, making abundant use of apocalyptic innuendo carried by terminology akin to Jewish apocalyptic theology and piety. Written against the background of modern day Christianity still grappling with law and the old paradigm two thousand years into new creation, this article hopes to share some of Paul’s vigour toward understanding the time we live in as post-law.